Prophylactic antibiotic use following cardiac arrest: A systematic review and meta-analysis. (August 2019) - Couper, Keith; Laloo, Ryan; Field, Richard; Perkins, Gavin D.; Thomas, Matthew; Yeung, Joyce
Abstract: Objective: To evaluate the effect of prophylactic/ early antibiotics (intervention group) compared with clinically driven/ delayed antibiotics (control group) on patient and infectious outcomes in adult cardiac arrest patients admitted to hospital. Data Sources: We searched MEDLINE (1946-current), EMBASE (1947-current) and the Cochrane library (inception-current) on 8th May 2018. Additional citations were identified through forward and backward citation tracking. Study Selection: Two reviewers independently screened titles, abstracts, and full-texts. We included observational and interventional primary research studies with a concurrent or retrospective control group that were relevant to our study objective. Data Extraction: We extracted data using a piloted data extraction form. Risk of bias was assessed using the Cochrane tool for randomised controlled trials or the GRADE tool for risk of bias in observational studies. Overall evidence quality for each outcome was assessed using the GRADE system. Data Synthesis: Databases searches and citation tracking identified 6825 citations, of which ten citations containing 11 studies (3 randomised controlled trials, 8 observational studies) were eligible for inclusion. Data were summarised in meta-analyses using random-effect models. The intervention was not associated with increased survival (odds ratio 1.16, 95% CI 0.97–1.40), survival with good neurological outcome (odds ratio 2.25, 95% CI 0.93–5.45), critical care length of stay (mean difference −0.6, 95% CI −3.6 to 2.4) or incidence of pneumonia (odds ratio 0.58, 95% CI 0.23–1.46). Findings were generally consistent between observational studies and randomised controlled trials. Conclusions: Antibiotic prophylaxis following cardiac arrest is not associated with a change in key clinical outcomes. Further high-quality trials may be needed to address this important clinical question. Review registration: PROSPERO CRD42016039358.